Influence of environmental factors on incidence of tuberculosis among patients of directly observed treatment short-course centers in Ibadan metropolis, Oyo State, Nigeria (2013)
Tuberculosis is one of the major diseases causing prolong ill health conditions especially in the developing countries of which Nigeria is one. It is a disease that is associated with poor environment. In other words, filthy environment can pave way for the disease. The study examined environmental factors influencing incidence of tuberculosis among patients in Directly Observed Treatment Short-Course Centres in Ibadan Metropolis, Oyo State, Nigeria. Descriptive survey research design was employed. Proportionate and simple random sampling techniques were used to select 206 respondents as sample for the study. Three research hypotheses were tested. Self - developed and validated sets of questionnaire were used to collect data. The descriptive statistics of frequency counts and percentages were used to analyse the demographic data, while chi - square (X2) and t - test were used to test the hypotheses at 0.05 alpha level. The finding showed that incidence of pulmonary tuberculosis was influenced by poor sanitary environment among patients of DOTS Centres in Ibadan Metropolis. It was also shown that there was no significant gender difference in factors that influenced among the patients. It was suggested that the State's Ministry of Health, non-governmental organisations and other stakeholders should intensify effort on public health education on environmental sanitation through symposia, seminars and conferences. State and Local Government Areas should strengthen the enforcement of environmental law and edit in Oyo State.